Scandium Reduced Arene Complex: Protonation and Reaction with Azobenzene. Issue 20 (2nd September 2021) - Ghana, Priyabrata; Spaniol, Thomas P.; Okuda, Jun
Abstract: The reactivity of the reduced anthracene complex of scandium [Li(thf)3 ][ScN( t Bu)Xy2 (anth)] (2‐anth‐Li ) (Xy=3, 5‐Me2 C6 H3 ; anth=C14 H10 2−, thf=tetrahydrofuran) toward Brønsted acid [NEt3 H][BPh4 ] and azobenzene is reported. While a stepwise protonation of 2‐anth‐Li with two equivalents of [NEt3 H][BPh4 ] afforded the scandium cation [ScN( t Bu)Xy2 (thf)2 ][BPh4 ] (3 ), reduction of azobenzene gave a thermolabile, anionic scandium reduced azobenzene complex [Li(thf)][ScN( t Bu)Xy2 ( η 2 ‐PhNNPh)] (4 ), which slowly lost one of the anilide ligands to form the neutral scandium azobenzene complex dimer [ScN( t Bu)Xy( μ ‐ η 2 : η 2 ‐Ph2 N2 )]2 (5 ). Exposure of 3 to CO2 produced the scandium carbamate complex [Scκ 2 ‐O2 CN( t Bu)(Xy)2 ][BPh4 ] (6 ) as a result of CO2 insertion into the Sc−N bonds. In an attempt to prepare scandium hydrides, the reaction of 3 with the hydride sources LiAlH4 and Na[BEt3 H] led to the terminal aluminum hydride [AlHN( t Bu)Xy2 (thf)] (7 ) and the scandium n ‐butoxide [ScN( t Bu)(Xy)2 ( μ ‐O n Bu)] (8 ) after Sc/Al transmetalation and nucleophilic ring‐opening of THF, respectively. All reported compounds isolated in moderate to good yields were fully characterized. Abstract : Scandium(III) anilide complex with the reduced anthracene is protonated to give a scandium cation. Reaction with azobenzene led to an anionic scandium reduced azobenzene complex that rearranges to a dimeric scandium reduced azobenzene complex.